Illumination Invariant Pre-Processing Techniques For Face Verification - Goh , Yi Zheng (2009)
This thesis is aimed to provide a mean to overcome the lighting control problem in face recognition by finding an algorithm to rid off illumination effects on facial image at the pre-processing stage. The proposed method adopted illumination-reflectance model to represent an illuminated facial image. In this work, three different illumination invariant pre-processing based methods have been proposed.